The Formation of the Future Tense in Slavonic Languages - Poljakov, Oleg (Slavistica Vilnensis, 2009)
The article considers the formation of the future tense in all groups of Slavonic languages. In Common Slavonic there were only some traces of the Proto I.E. s-future tense and the new future tenses appeared later in separate groups of Slavonic languages after disintegration of their common ancestor. Their formation had different peculiarities. In East and West Slavonic languages the formation of future tenses was an internal Slavonic process, whereas South Slavonic languages were influenced by some common developments inside of Balkan’s languages. It may be assumed that the innovation center was the Greek language. The article provides some insights into the development of various future forms in Slavonic languages.